Alat Penghancur Kulit Kayu Manis Berbasis PLC - Tua, Parohon Maruli (MASALIQ, 2025)
This study presents the design and development of an automated cinnamon bark shredder control system using a Programmable Logic Controller (PLC). The purpose of the system is to enhance production efficiency by replacing manual processes with automation, thereby reducing time, labor costs, and error rates. The system integrates components such as proximity sensors, induction motors, and PLC Omron CP1E, programmed with the CX-Programmer software. Testing demonstrated that the shredder effectively processes cinnamon bark into fine powder meeting Indonesian National Standards (SNI) for export, with consistent results in particle size (0.7–1 cm) and reduced waste. The tool is suitable for small and medium-sized industries (IKM) due to its cost efficiency, operational simplicity, and ability to improve production capacity. Future developments may focus on scaling up for industrial use.